Association of Level of Physical Exertion with Acute Myocardial Infarction in Bangladeshi Population - Azad, Md Kamrul; Chowdhury, Abdul Wadud; Rahman, Mohammad Arifur; Arafat, Shohael M; Ahmed, Sheikh Foyez; Dastider, Sathi (Cardiovascular Journal, 2016)
Background: Evidences suggest that heavy physical exertion can trigger the onset of acute myocardial infarction. But there have been no clean cut data in Bangladesh about the risk of myocardial infarction during and after heavy exertion. To address this question the study was conducted. Methods: It was a multicentre cross sectional study was conducted from July 2012 to June 2013 with patient of diagnosed acute myocardial infarction (AMI) admitted in department of cardiology of National Institute of Cardiovascular Diseases (NICVD), Bangabandhu Sheikh Mujib Medical University (BSMMU) and Dhaka Medical College Hospital (DMCH). From selected samples, two hours activity prior to onset of symptom of AMI was asked according to standard questionnaire. Activities were quantified on a scale from 1 to 8 metabolic equivalents (METs) according to generally accepted values. Collected data were analyzed by SPSS version 16. Results: In this study 246 patients (74 .4 percent of whom were men; mean age [±SD], 64.68 ± 7.63 years) were interviewed. The study showed that 11.38% patients were engaged in strenuous physical exertion (e 6 METs) within two hours prior to symptom onset of AMI. Strenuous exertion group of AMI patients were all most all sedentary worker [26 (92.86%) of 28]. Most of the patients (82.14 %) of strenuous group had history of less than 8 hours work per day. Strenuous exertion group had history of longtime exertion (72.57%, 1-2 hours) than non-strenuous group (42.66%, <0.5 hours). Moreover, 67.86% AMI patients of strenuous exertion group had experienced irregular exertion whereas most of the patients (64.22%) of non strenuous group had a history of regular exertion. Conclusions: The result of the study indicates that a period of strenuous physical activity is associated with increased risk of having AMI, particularly among patients of sedentary worker who have dyslipidemia and who exercise irregularly. Those who exercise regularly have lower chances of AMI as shown by the negative correlation. Cardiovasc. j. 2016; 8(2): 115-122